2021
DOI: 10.1007/s00227-021-03971-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural thermoregulation linked to foraging in blue sharks

Abstract: Large pelagic fishes often dive and surface repeatedly as if they were airbreathers, raising a question about the functions of these movements. Some species (e.g., bigeye tuna, ocean sunfish) apparently alternate foraging in deep cold waters and rewarming in shallow warm waters. However, it is unclear how prevalent this pattern is among species. Blue sharks are the widest-ranging pelagic shark with expanded vertical niches, providing a model for studying foraging-thermoregulation associations. We used electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
2
21
1
Order By: Relevance
“…Furthermore, blue sharks swiftly end their deep dives when muscle cools to 15°C, with a range of water temperature met during the dives spanning from 7 to 26°C (Carey et al, 1990). While finding the same minimum muscle temperature, Watanabe, Nakamura, and Chiang (Watanabe et al, 2021) concluded that the regular deep-diving behavior of this species can be parsimoniously explained by their motivation for maintaining body temperature within a narrow range while foraging in the stratified water columns. Overall, blue shark classes have variable tolerance to minimum temperature (LJF < SJ < [LJM, AF] < AM), which is valuable habitat information for identifying bycatch mitigation measures targeting the most vulnerable classes.…”
Section: Consistency Of Model Results With Known Traits and Habitatsmentioning
confidence: 98%
“…Furthermore, blue sharks swiftly end their deep dives when muscle cools to 15°C, with a range of water temperature met during the dives spanning from 7 to 26°C (Carey et al, 1990). While finding the same minimum muscle temperature, Watanabe, Nakamura, and Chiang (Watanabe et al, 2021) concluded that the regular deep-diving behavior of this species can be parsimoniously explained by their motivation for maintaining body temperature within a narrow range while foraging in the stratified water columns. Overall, blue shark classes have variable tolerance to minimum temperature (LJF < SJ < [LJM, AF] < AM), which is valuable habitat information for identifying bycatch mitigation measures targeting the most vulnerable classes.…”
Section: Consistency Of Model Results With Known Traits and Habitatsmentioning
confidence: 98%
“…However, these may be overestimates because our model assumed that sharks were stationary relative to the water flow, which can be 300% more hydrodynamically efficient than a swimming fish undulating body (23). In addition, Watanabe et al (24) recently reported that gliding behaviour accounted for only 10% and 20% of total descent duration of tagged blue sharks, equating to less than 5 to 10% of the time during the typical yoyo-diving behaviour (25). The G-Pilot tags produce significantly lower drag penalties for blue sharks, close to the 5% threshold for animals larger than 2.5 m and are thus more suited to investigate the ecology of mature blue sharks and other slender-bodied sharks.…”
Section: Discussionmentioning
confidence: 96%
“…5 ms -1 , fig. 10,(24,25). The towed G-Pilot tag successfully quantified swimming performance, depth and temperature, and yielded precise geolocations of tagged sharks and mobulas, and thus is a valuable tool for short-term studies where high-resolution data is required and fixed tags are not an option.…”
mentioning
confidence: 99%
“…Acute body temperature elevations have been known to cause a number of physiological, ecological and behavioural consequences; in terms of physiology, rapid elevations of body temperature can speed up digestion rates ( Carey et al, 1984 ), increase the expression of heat shock proteins ( Renshaw et al, 2012 ) and affect biological rates, such as metabolism ( Morley et al, 2019 ), potentially contributing to a deficit in the sharks’ daily energy budget, as has been shown before ( Bouyoucos et al, 2017 , 2018 ). Regarding behavioural changes, elevations of body temperature can result in distributional changes as sharks are known to adjust their position in the water column as a means to behaviourally thermoregulate ( Sims et al, 2006 ; Nakamura et al, 2020 ; Watanabe et al, 2021 ), or may expand their horizontal range if topographically limited (e.g. the tiger sharks in the Bahamas are depth limited and therefore may travel further offshore to seek out colder, deep waters) ( Gallagher et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%